Strategies for Shariah Financial Literacy among Teachers: A Mental Accounting Approach - R. Suryanti Ismail; Marissa Silooy; Yosmina T.Titaley (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This research aims to optimize sharia financial literacy among Muslim teachers at the Al-Hilaal Foundation, Ambon City, using a mental accounting approach. The study addresses the lack of understanding of Islamic financial principles and rational financial management among educators, who serve as vital agents of change in society Method: The study utilized a "pre-test and post-test one-group design". Data were collected from 20 teachers through questionnaires measuring sharia literacy and mental accounting concepts. Interventions included interactive lectures, discussions, and the distribution of training modules. Practical Applications: The findings demonstrate that integrating financial psychology with sharia values effectively improves financial behavior. This approach can be replicated in other educational institutions to enhance educators' economic well-being and prudent financial decision-making.  Conclusion: The intervention significantly increased participants' understanding of sharia financial management and behavior. The integration of mental accounting and maqāṣid al-sharī'ah provides a robust framework for developing sustainable financial mindsets that bridge rational and spiritual dimensions.